China Quest for Global Predominance. (2nd January 2020) - Shlapentokh, Dmitry
Abstract: China's elite have clear plans for global predominance based on its economic clout. Ideologically, it is framed in a peculiar blend of Marxism and China's traditional philosophy. China's trade policy and drive to receive needed natural resources, such as gas, fits in with these generations-long plans. Beijing has taken into consideration not just purely economic but also geopolitical implications. Following this model, Beijing appeals either to Moscow or Washington and changes the engagement pattern to achieve the desired result. Although using one power against the other is not a peculiarly Chinese way of dealing with outsiders, China has a clear advantage, for its totalitarian government could plan for generations and could change course regardless of the wishes of the electorate or clearly defined interest groups, as is the case with the modern capitalist West.